Barriers and solutions towards a circular economy in Walloon SEs and SMEs - Muguerza, Arnaud (2019)
The circular economy is a new economic model based on natural ecosystems. Its objective is to promote closed-loop cycles to replace the current linear economy. The aim of this dissertation will be to analyse how far Walloon companies are concerned with the circular economy. We will examine the barriers to a successful transition and determine the most effective solutions and levers to be implemented. Following a thematic analysis approach, we did a qualitative study by conducting semi-structured interviews with different actors on the field and within companies taking and not taking part in the circular economy. The main barriers for companies not acting in a circular way are the technical and cognitive barrier. For companies in the circular economy, many face a financial brake as well. Different levers are detailed as part of a solution towards a successful implementation in Wallonia, like the necessity of regulatory changes or the importance of partnerships inside industries and geographical areas. Finally, our discussion confronts theory with practice and the author’s contribution is clearly mentioned.